2010
DOI: 10.1038/bmt.2010.304
|View full text |Cite
|
Sign up to set email alerts
|

A prospective evaluation of patients' health-related quality of life during auto-SCT: a 3-year follow-up

Abstract: Few studies have evaluated long-term health-related quality of life (HRQL) in patients during auto-SCT. This prospective study examined HRQL in 96 eligible patients before, during and up to 3 years after auto-SCT. The aim of the study was to make a comprehensive assessment of the frequency and severity of different symptoms in patients undergoing auto-SCT. The European Organization for Treatment and Research of Cancer Quality of Life Questionnaire (EORTC QLQ C-30) was administered 13 times. The second week dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
33
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 35 publications
(39 reference statements)
2
33
0
Order By: Relevance
“…We observed that PF, SF and CF as well as global QOL deteriorated, while EF improved over time. This pattern has been documented in other longitudinal studies using the QLQ-C30 ; domain scores related to physical function diminished from pre-treatment to on- or immediately after treatment and emotional function improved [20]. The initial anxiety of the diagnosis and treatment initiation period may have been ameliorated by subsequent familiarity and supportive psychosocial care provided by the clinical service teams.…”
Section: Discussionsupporting
confidence: 63%
“…We observed that PF, SF and CF as well as global QOL deteriorated, while EF improved over time. This pattern has been documented in other longitudinal studies using the QLQ-C30 ; domain scores related to physical function diminished from pre-treatment to on- or immediately after treatment and emotional function improved [20]. The initial anxiety of the diagnosis and treatment initiation period may have been ameliorated by subsequent familiarity and supportive psychosocial care provided by the clinical service teams.…”
Section: Discussionsupporting
confidence: 63%
“…At the time of hospital discharge, the average severity of sleep disruption among allogeneic and autologous patients was still moderately elevated relative to baseline symptomatology (i.e., .51 SD) (26). Nevertheless, it appears that increases in sleep disruption are generally transient; by day 100, sleep disruption returns to levels comparable to pre-HCT (4, 25, 31), although these levels are substantially elevated even before the transplant. Patients receiving allogeneic HCT demonstrate similar levels of sleep disruption near day 100 to patients receiving autologous transplant (4).…”
Section: Sleep Disruption and Disorders During The Acute Transplant Pmentioning
confidence: 97%
“…Sleep disruption significantly increased during the first 100 days, with greatest disruption seen during the conditioning regimen and white blood cell count nadir (31). Mean changes of 27 points on the EORTC QLQ-C30 sleep disruption item were observed from pre-transplant baseline to its peak approximately two weeks post-HCT (25), corresponding to a large increase and effect size of 1.1 standard deviations (SD) (25). These data are consistent with a recent quantitative review of all published studies using the EORTC QLQ-C30 to assess quality of life in HCT patients, which found large increases in sleep disruption during hospitalization (26).…”
Section: Sleep Disruption and Disorders During The Acute Transplant Pmentioning
confidence: 99%
“…QOL is increasingly assessed as a secondary endpoint in clinical trials as well as a main focus of observational research. Consequently, there is now a sizable body of research that is published or underway comparing QOL in various treatment regimens and describing changes in QOL during the transplant process (3-8). …”
mentioning
confidence: 99%